Utility of quantitative whole-body autoradiography (QWBA) and oxidative combustion (OC) analysis in the assessment of tissue distribution of [14C]Mefuparib (CVL218) in SD and LE rats. - Xinmei Li; Feiyu Wang; Xinyue Zhang; Xiaokun Shen; Chunhao Yang; Yuandong Zheng; Xingxing Diao (PLoS ONE)
Background In tissue distribution studies of radiopharmaceuticals, quantitative whole-body autoradiography (QWBA) and oxidative combustion (OC) analysis are the two important methods that have not been compared using the same drug. Sprague-Dawley (SD) and Long-Evans (LE) rats, both of which are commonly used rodents in tissue distribution studies, have also not been compared using the same drug. Comparative studies are important for aiding the selection of appropriate experimental methods and animals. Methods To evaluate the tissue distribution of [14C]Mefuparib (CVL218) in rats and assess its clinical safety, QWBA and OC analysis were used. The differences between the two methods were noted. Comparisons between the tissue distribution results of LE and SD rats were also done. Results The QWBA and OC distribution analysis showed that [14C]CVL218-related radioactivity could be distributed in 19 tissues. For 89.47% of the tissues, no significant differences were noted between the two methods. There were also no differences in the pharmacokinetics data for plasma and brain homogenates between LE and SD rats. However, the pharmacokinetics data for liver and kidney homogenates were seven-fold higher in LE rats than in SD ones. Conclusions Both the OC and QWBA methods revealed that [14C]CVL218 could be widely distributed in the tissues of rats. The OC had a lower limit of quantification while QWBA provided a more comprehensive analysis of [14C]CVL218 distribution. More safety was associated with using LE rat data to estimate the dosimetry of [14C]CVL218 for the whole-body, for human radiolabeled mass balance studies.